2023
DOI: 10.1186/s12891-023-06207-1
|View full text |Cite
|
Sign up to set email alerts
|

Singapore KneE osTeoarthritis CoHort (SKETCH): protocol for a multi-centre prospective cohort study

Abstract: Background Knee osteoarthritis (OA) is a leading cause of global disability. The understanding of the role of psychosocial factors in knee OA outcomes is still evolving particularly in an Asian context. The primary aim of this study is to explore psychosocial factors that prognosticate short and long-term clinical outcomes, productivity, and healthcare utilization in patients with knee OA. Secondary aims are to explore the mediation and directional relationships and the role it plays in predict… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 68 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…It reduces respondent burden by 70% from the original KOOS while providing scale scores for knee-specific pain, function, and QOL, along with a summary measure of overall knee impact [ 40 ]. The KOOS score has been validated in Singapore [ 39 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…It reduces respondent burden by 70% from the original KOOS while providing scale scores for knee-specific pain, function, and QOL, along with a summary measure of overall knee impact [ 40 ]. The KOOS score has been validated in Singapore [ 39 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…This study analyzed baseline data collected as part of a pre-registered (clinicaltrials.gov, NCT04942236 first registered 28/06/2021) multi-center, prospective cohort study for people with knee osteoarthritis in Singapore [ 24 ]. This study is reported following the STROBE guidelines [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Existing large, international cohort studies focus primarily on biological factors such as radiographic imaging and biomarkers [13, 16]. Recent efforts have started to lay the groundwork for large longitudinal cohorts focusing on psychosocial factors [18].…”
Section: How Do We Get There?mentioning
confidence: 99%